A Systems and procedures study on power wheels - Bajar, Jean Corinna H.; Limcaoco, Katrina K.; Santos, Jovito U.; Tan, Patricia Anna C.; Valencia, Felicidad D.L (College of Engineering, 1989)
This systems and procedures study on power wheels car center covers the following areas : work distribution among the company's office employees and the flow of the company's processes, mainly those with corresponding flow of forms.